The night fairy - Schlitz, Laura Amy.; Barrett, Angela (Somerville, Mass. : Candlewick Press, 2010)
When Flory the night fairy's wings are accidentally broken and she cannot fly, she has to learn to do everything differently.
Horn Book
Publisher's Weekly
School Library Journal starred
Bulletin (Center for Children's books), February 2010
Horn Book, March 2010
Library Media Connection, May 2010
Keywords: Fairies -- Juvenile fiction; Friendship -- Juvenile fiction; Magic -- Juvenile fiction; Adventure and adventurers -- Fiction; Fairies -- Fiction; Friendship -- Fiction; Magic -- Fiction; Adventure fiction; Fairies -- Fiction; Friendship -- Fiction; Magic -- Fiction; Adventure fiction